A flame retarded chitosan binder for insulating miscanthus/recycled textile fibers reinforced biocomposites. Issue 13 (25th November 2018) - El Hage, Roland; Khalaf, Yasmina; Lacoste, Clément; Nakhl, Michel; Lacroix, Patrick; Bergeret, Anne
ABSTRACT: The main objective of this study is devoted to the development of new insulating and ignifuged miscanthus fibers (Mf)/recycled textile fibers (RTf) reinforced biocomposites (BCs) using chitosan as polysaccharide‐based binder and aluminum trihydroxide (ATH) fillers while focusing on the fire behavior. To achieve this goal, a preliminary study was carried out on flame retarded chitosan‐based films with various ATH‐filler ratios (20, 33, 50, and 60 wt %). ATG and pyrolysis‐combustion flow calorimeter analysis showed significant improvement of chitosan thermal behavior with the addition of 33 wt % and above of ATH. Mechanical properties of films were, however, degraded. Thereafter, different ratios of miscanthus/RTf reinforced BCs (fibers content up to 89.5–90 wt %) were elaborated through thermocompression process using neat chitosan and chitosan/ATH (67/33 wt %) as a binder. Mechanical, thermal, and fire behavior were evaluated. Higher mechanical properties were found for hybrid materials containing the association of both RTf and Mf in comparison to those containing only RTf or Mf. Fireproof BCs (E rating: according to the NF EN ISO 11925‐2), with thermal conductivity values between 0.07 and 0.09 W m −1  K −1 and density range between 270 and 299 kg m −3 were successfully elaborated. The results of this study show a promising use of the chitosan/ATH system as flame retardant for biobased insulating building materials. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47306. Abstract :